Retinal Wave Patterns Are Governed by Mutual Excitation among Starburst Amacrine Cells and Drive the Refinement and Maintenance of Visual Circuits - Xu, Hong-Ping (J Neurosci, 2016)
Retinal waves are correlated bursts of spontaneous activity whose spatiotemporal patterns are critical for early activity-dependent circuit elaboration and refinement in the mammalian visual system. Three separate developmental wave epochs or stages have been described, but the mechanism(s) of pattern generation of each and their distinct roles in visual circuit development remain incompletely understood. We used neuroanatomical, in vitro and in vivo electrophysiological, and optical imaging techniques in genetically manipulated mice to examine the mechanisms of wave initiation and propagation and the role of wave patterns in visual circuit development. Through deletion of β2 subunits of nicotinic acetylcholine receptors (β2-nAChRs) selectively from starburst amacrine cells (SACs), we show that mutual excitation among SACs is critical for Stage II (cholinergic) retinal wave propagation, supporting models of wave initiation and pattern generation from within a single retinal cell type. We also demonstrate that β2-nAChRs in SACs, and normal wave patterns, are necessary for eye-specific segregation. Finally, we show that Stage III (glutamatergic) retinal waves are not themselves necessary for normal eye-specific segregation, but elimination of both Stage II and Stage III retinal waves dramatically disrupts eye-specific segregation. This suggests that persistent Stage II retinal waves can adequately compensate for Stage III retinal wave loss during the development and refinement of eye-specific segregation. These experiments confirm key features of the “recurrent network” model for retinal wave propagation and clarify the roles of Stage II and Stage III retinal wave patterns in visual circuit development. SIGNIFICANCE STATEMENT Spontaneous activity drives early mammalian circuit development, but the initiation and patterning of activity vary across development and among modalities. Cholinergic “retinal waves” are initiated in starburst amacrine cells and propagate to retinal ganglion cells and higher-order visual areas, but the mechanism responsible for creating their unique and critical activity pattern is incompletely understood. We demonstrate that cholinergic wave patterns are dictated by recurrent connectivity within starburst amacrine cells, and retinal ganglion cells act as “readouts” of patterned activity. We also show that eye-specific segregation occurs normally without glutamatergic waves, but elimination of both cholinergic and glutamatergic waves completely disrupts visual circuit development. These results suggest that each retinal wave pattern during development is optimized for concurrently refining multiple visual circuits.